Bronchopulmonary sequestration with massive pleural effusion: pleuroamniotic shunting vs intrafetal vascular laser ablation. (2nd September 2014) - Mallmann, M. R.; Geipel, A.; Bludau, M.; Matil, K.; Gottschalk, I.; Hoopmann, M.; Müller, A.; Bachour, H.; Heydweiller, A.; Gembruch, U.; Berg, C.
ABSTRACT Objective To assess the incidence of complications among a relatively large cohort of fetuses with bronchopulmonary sequestration (BPS) and the success of two different intrauterine treatment modalities. Methods All cases with a prenatal diagnosis of BPS detected in a 10‐year period (2002–2011) in two tertiary referral centers were reviewed retrospectively for intrauterine course and outcome. Up to May 2010 severe pleural effusions were treated with pleuroamniotic shunting. Thereafter, they were treated with ultrasound‐guided laser coagulation of the feeding artery. Results A total of 41 fetuses with BPS were included in the study. In 29 (70.7%) there was no pleural effusion or hydrops and they were treated conservatively. In 19/29 (65.5%) there was partial or complete regression of the lesion during the course of pregnancy. All were born alive (median age at delivery, 38.3 (interquartile range (IQR), 34.0–39.6) weeks) and 16 (55.2%) required sequestrectomy. Intrauterine intervention was performed in all 12 (29.3%) fetuses with pleural effusion. Seven fetuses were treated with pleuroamniotic shunting. One fetus with severe hydrops died in utero. There was no complete regression in any case of BPS in this group. Six infants were born alive (median age, 37.2 (IQR, 30.3–37.4) weeks), of which five (83.3%) required sequestrectomy. Five fetuses were treated with laser ablation of the feeding vessel. In all cases of BPS there was regression after laser ablation. All infants were delivered at term (median age, 39.1 (IQR, 38.0–40.0) weeks). One (20.0%) neonate required sequestrectomy after birth. Following intrauterine shunt placement complete regression of the lesion was significantly less frequent (0/7 (0%) with shunt placement vs 4/5 (80%) with intrafetal laser treatment) and gestational age at birth was significantly lower, compared to treatment with intrafetal laser. Complete regression of the lesion was also significantly more frequent in the laser group compared to cases without intervention. Conclusion In the absence of pleural effusion, the likelihood of spontaneous regression of BPS is high and the prognosis is therefore favorable. In cases with massive pleural effusion, treatment by laser ablation of the feeding vessel seems to be more effective than is pleuroamniotic shunting, with fewer complications. It might also reduce the need for postnatal surgery. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.